Enrichment of lecithin with phenolics from olive mill wastewater by cloud point extraction and its application in vegan salad dressing. Issue 7 (9th May 2022) - Karadag, Ayse; Kayacan Cakmakoglu, Selma; Metin Yildirim, Rusen; Karasu, Salih; Avci, Esra; Ozer, Hayrettin; Sagdic, Osman
Abstract: In this study, the phenolic compounds of oil mill waste (OMW) were extracted through the cloud point extraction method using lecithin as a surfactant. For this purpose, the effects of the equilibration temperature and time, pH, and the concentration of NaCl and lecithin on the recovery (%) of total phenolic content (TPC) were investigated by single‐factor experiments and further optimization of the process variables was carried out using the response surface analysis. The TPC values of OMW were 4830.50 ± 414.7 mg GAE/L, 7545.25 ± 766.89 TyE/L, and 5220.22 ± 390.68 HyTE/L. Antioxidant capacity values were 6892.05 ± 222.64 mg TE/L, 5010.54 ± 216.90 mg Fe 2+ E/L, and 4315.06 ± 237.73 mg TE/L. Hydroxytyrosol was the main phenolic compound identified with the value of 592.91 ± 8.39 mg/L followed by tyrosol at the level of 167.34 ± 2.23 mg/L. The optimum process conditions were determined as the temperature of 65°C, pH of 4.5, NaCl concentration of 10% (w:v), and lecithin concentration of 15% (w:v). The enriched lecithin obtained under the optimum conditions was used in the formulation of salad dressing, and its oxidative stability as compared to the sample prepared by control lecithin. The results obtained from oxidation kinetic parameters namely, IP, E a, Δ H ++ ∆ S ++, and ∆ G ++ showed that the salad dressings prepared with enriched lecithin provided higher oxidative stability than control lecithin. This study suggested that the use of lecithin in cloud point extraction could offer a new perspective for the recovery of phenolics from OMW without the application of solvent. Practical applications: During the production of olive oil, waste with high biological value, rich in phenolic compounds, is generated. The recovery of phenolics from this waste and their use in the food industry is one of the current issues. Most of the studies on this subject are attempts to recover phenolics using solvents. The use of solvents limits the recovery efficiency of the OMW phenolics and their use in the food industry. Therefore, alternative methods are needed for the recovery of OMW phenolics. This study aimed to recover OMW phenolics with the cloud point extraction method, in which lecithin is used as a surfactant. Lecithin was used for this purpose for the first time in this study. Thus, it is aimed to produce enriched lecithin, which can be used directly in the food industry, as well as provide the recovery of olive oil waste phenolics without using solvents.